An Apprehension and Decoding of Phonetic (English Sound Symbols) by Juxtaposing Hindi Alphabets (Indian knowledge System) : A Critical Perspective for Indian Students - Arora, Poornima; Tiwari, Deepti; Kulshreshtha, Sangeeta; Geetey, Shreya; Ramawat, Ritika; Pundhir, Manya; Ansari, Alina; Rajendren Nayagi, Soundara (Journal of Neonatal Surgery, 2025)
English spelling-to-sound inconsistencies present a significant obstacle for Indian learners of English, for whom Hindi’s one-to-one grapheme–phoneme correspondence offers a more transparent model. This study proposes an innovative, L1-based decoding approach that leverages Hindi’s Varṇamālā—specifically its Svar (vowel) and Vyanjan (consonant) letters—to facilitate the learning of English phonetic sound symbols. Through a comparative analysis of English orthography and phonetic transcription, we (1) delineate the fundamental divergences between English alphabet letters and International Phonetic Alphabet (IPA) symbols; (2) develop an accessible mapping of English monophthongs onto Hindi Svar and Vyañjan categories; and (3) introduce a tailored framework for mastering English diphthongs via structured analogies to Hindi vowel sequences. By grounding English pronunciation instruction in learners’ native phonological knowledge, this methodology aims to enhance phonemic awareness, reduce pronunciation errors, and foster greater confidence in spoken English. The proposed L1-anchored strategy holds promise as a user-friendly tool for second-language pronunciation training.